Susceptibilidad de Mycobacterium fortuitum, Mycobacteriun phlei y Mycobacteriun kansasii frente a tres soluciones germicidas - Oriani, D.S. (2005)
An investigation was carried out to measure the in vitro susceptibility of opportunistic mycobacteria to three antimicrobial agents. Field strains of nontuberculous mycobacteria were obtained of soil samples from La Pampa province (Argentina). Strains of the following species were tested: Mycobacterium fortuitum, M. phlei and M. kansasii. The antimicrobial agents were: 2% and 4% formaldehyde solutions, 3% and 5% phenol solutions and 70% alcohol solution. At 20o C, suspensions of the test strains were exposed to the germicides and samples were taken at defined intervals (25 min and 45 min) to determine the concentration of survivors. From these data, the decimal reduction times (D) were calculated for each test strain. The results obtained indicated that the nontuberculous mycobacteria were resistant to formaldehyde 2% during 25 min. The D values found revealed considerable differences in the chemical susceptibilities of the test strains. However, all the tested strains were susceptible to formaldehyde 4%, phenol solutions, and alcohol solution 70%. It is necessary to continue evaluating other germicide agents and their effects on Mycobacterium bovis in order to find effective disinfectants for animal waters and field facilities, thus contributing to the control of tuberculosis in cattle.